2018
DOI: 10.2147/ndt.s169051
|View full text |Cite
|
Sign up to set email alerts
|

Internalized stigma and its correlates among patients with severe mental illness

Abstract: PurposeThe aim of this study was to investigate the perceived level of internalized stigma among patients with severe mental illnesses and its relationship with demographic and clinical variables in Poland.Patients and methodsA study sample (n=114, mean age=42.46±14.1 years; 55% of females) consisting of patients with nonorganic psychotic disorders as well as unipolar and bipolar affective disorders was evaluated (58% of outpatients and 39% of inpatients). All patients filled in the Internalized Stigma of Ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
31
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 25 publications
7
31
2
Order By: Relevance
“…Higher levels of prejudicial and stigmatizing attitudes have also been reported by individuals experiencing suicidal ideation or who have attempted suicide [59]. Mental illness severity has previously been identified as a predictor of stigma among people with mental health problems [62,63]. In our study, participants with alcohol abuse were also more likely to be a member of the high discrimination trajectory group, and those with substances dependence tended to be part of the moderate to high stigma group trajectory.…”
Section: Discussionsupporting
confidence: 58%
“…Higher levels of prejudicial and stigmatizing attitudes have also been reported by individuals experiencing suicidal ideation or who have attempted suicide [59]. Mental illness severity has previously been identified as a predictor of stigma among people with mental health problems [62,63]. In our study, participants with alcohol abuse were also more likely to be a member of the high discrimination trajectory group, and those with substances dependence tended to be part of the moderate to high stigma group trajectory.…”
Section: Discussionsupporting
confidence: 58%
“…Having no history of suicidal attempt to decrease the stigma score as compared to having a history of suicidal attempt in this study but finding from Poland indicates suicidal attempt not associated with internalized stigma [26]. This difference might be due to our study is specific to mood disorders which have a high risk of suicide.…”
Section: Discussioncontrasting
confidence: 50%
“…Low self-esteem, hope, and well-being, general functioning, age, sex, income, unemployment, education, duration of illness, adherence, having depressive episode, duration of illness, poor social support, presence of medication side effect, recovery, severity of symptoms, insight, family history of mental illness and substance use were factors associated with internalized stigma [10,12,[24][25][26][27][28][29][30][31][32].…”
mentioning
confidence: 99%
“…Having chronic major depressive disorder of ≥2-year duration was 3.21 times more likely to have a high internalized stigma than those who have less than 2 years of duration of illness. This is supported by different studies conducted in India [17] and Poland [20]. The possible reason for this association might be long-lasting poor social and occupational functioning resulting from the illness.…”
Section: Discussionmentioning
confidence: 55%
“…Most studies done in western and Asian countries show that a high magnitude of internalized stigma among patients with depressive disorder ranges from 21.7 to 51.4% [17][18][19][20][21][22][23]. Accordingly, a study done in 13 European countries assessed the levels of internalized stigma among patients with mood disorders and they found that moderate to high levels of internalized stigma is present in 21.7% of individuals [4].…”
Section: Introductionmentioning
confidence: 99%